Educação, formação e profissionalização docente no Brasil e no Timor-Leste - Ferreira, Manuel (2011)
This study links to research line Teaching training and Professionalisation. The work aims to address the perspective that are discussed in teacher training and professionalisation, taking as a principal basics, especially the writings of Guimarães (2004, 2006), Tardif (2002), Charlot (2005), Contreras (2002), Cunha (1999), Lüdke (2008), Nóvoa (1995, 1999), among the others. Are addressed the basics of teacher training and teacher professionalization perspectives, characterised as: (1) sociology of professions; (2) official Discourse; (3) socio-historical; and (4) the specificity of the teaching profession. From these basic aspects and perspectives, seeks to identify under which aspects of the aspects process the Brazilian teachers training and professionalisation can inspire the education, teachers training and professionalisation constitution of East Timor. The methodological perspective of this work is the bibliographic search and the methodical standpoint is that of dialectical and historical materialism. Under these optical methodical, sought to make a systematic analysis of national and foreign literature (including official documents of the speeches), released in Brazil on the subject, trying to understand the training and professionalisation of teacher in its historical context, looking to associate it to other professions, including them in their specificity and associating them to the reality of the Brazilian teacher training and Timorese. The result of this study reveals that the discussions on training and professionalization in recent years in Brazil had more emphasis on educational policies in the educational process leading to political-economic interests. As consequences of these interests, disengaged the education of its main goals, contributing to his disqualification and vulnerability of teachers. The movement for improving arose, primarily through the academic context, giving importance to building appreciation and knowledge of professionals, involving aspects such as: redefinition of the profession of the teacher, from the perspective of their specificity, calling attention to improve their professional status. In the framewark of these discussions, it was examined whether identify contributions of these theoretical perspectives that can inspire the education, teacher training and professionalisation in East Timor. Keyword: